KAUSALITAS SUKU BUNGA DOMESTIK DENGAN TINGKAT INFLASI DI INDONESIA - Purnomo, Didit (Universitas Muhammdaiyah Surakarta, 2004)
This research discusses about the correlation pattern between inflation rate and interest rate, in other word this causality called inflation rate-interest rate causality. This research uses 1984-2001 data and we have conclude that interest rate have a significant effect to inflation rate. By using granger causality model, we could have a conclusion that the correlation pattern between interest rate and inflation rate in Indonesia is interest rate causes inflation.